2019
DOI: 10.1523/jneurosci.0593-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Learning What Is Irrelevant or Relevant: Expectations Facilitate Distractor Inhibition and Target Facilitation through Distinct Neural Mechanisms

Abstract: It is well known that attention can facilitate performance by top-down biasing processing of task-relevant information in advance. Recent findings from behavioral studies suggest that distractor inhibition is not under similar direct control but strongly dependent on expectations derived from previous experience. Yet, how expectations about distracting information influence distractor inhibition at the neural level remains unclear. The current study addressed this outstanding question in three experiments in w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
97
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 116 publications
(125 citation statements)
references
References 61 publications
17
97
1
Order By: Relevance
“…Similarly, in search tasks, subjects are faster in responding to targets when a distractor is presented more often at one of the search locations, that is, when its location has become predictable. Crucially, this benefit of distractor predictability cannot be explained by more attention to the remaining possible target locations or mere priming . Of further note, observers are typically unaware of the unequal probability of distractor occurrences across display locations, indicating that this form of suppression relies on implicit learning mechanisms, that is, is not dependent on working memory .…”
Section: Indirect Preparatory Distractor Suppressionmentioning
confidence: 97%
See 4 more Smart Citations
“…Similarly, in search tasks, subjects are faster in responding to targets when a distractor is presented more often at one of the search locations, that is, when its location has become predictable. Crucially, this benefit of distractor predictability cannot be explained by more attention to the remaining possible target locations or mere priming . Of further note, observers are typically unaware of the unequal probability of distractor occurrences across display locations, indicating that this form of suppression relies on implicit learning mechanisms, that is, is not dependent on working memory .…”
Section: Indirect Preparatory Distractor Suppressionmentioning
confidence: 97%
“…Of further note, observers are typically unaware of the unequal probability of distractor occurrences across display locations, indicating that this form of suppression relies on implicit learning mechanisms, that is, is not dependent on working memory . In direct support of the notion that statistical distractor learning does not rely on working memory, Gao and Theeuwes recently showed that learning to suppress distracting information was not affected by the load of a concurrent working memory task.…”
Section: Indirect Preparatory Distractor Suppressionmentioning
confidence: 99%
See 3 more Smart Citations